Revisiting Non-BRCA1/2 Familial Whole Exome Sequencing Datasets Implicates NCK1 as a Cancer Gene - Yin, Jie; Wu, Kai; Ma, Qingyang; Dong, Hang; Zhu, Yufei; Hu, Landian; Kong, Xiangyin (Frontiers in Genetics, 2019)
Through linkage and candidate gene screening, many breast cancer predisposition genes have been identified in the past twenty years. However, majority of genetic risk contributing to familial breast cancer is still undetermined. In this study, we revisited whole exome sequencing datasets from non-BRCA1/2 familial breast cancer patients to search for novel breast cancer predisposition genes. Based on the infinite mutation model, we supposed that rare non-silent variants cooccurred between familial and TCGA-germline datasets might have the predisposition contributing role. In our analysis, we not only identified novel potential pathogenic variants from known cancer predisposition genes, such as MRE11, CTR9 but also identified novel candidate predisposition genes, such as NCK1. According to TCGA mRNA expression dataset of breast cancer, NCK1 was significantly upregulated in basal-like subtypes and downregulated in luminal subtypes. In vitro, NCK1 mutants (D73H and R42Q) transfected MCF7 cell lines, which attributed to luminal subtype, were much more viable and invasive than wild type. On the other side, our results also showed that overall survival and disease-free survival of patients with NCK1 variations might be genomic context dependent. In conclusion, genetic heterogeneity exists among non-BRCA1/2 breast cancer pedigrees and NCK1 could be a novel breast cancer predisposition gene.